STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MENULIS DENGAN METODE DRILL DI KELAS 1 C DI SDS ISLAM TERPADU SULTHONIYAH SAMBAS TAHUN PELAJARAN 2022-2023 - Triyana (Lunggi Journal, 2024)
This thesis discusses teacher strategies in improving skills with the drill method in grade I C of integrated Islamic private elementary schools sulthoniyah sambas for the 2022-2023 academic year. The research has three objectives, namely: 1) To describe strategic planning in improving writing skills with the drill method in grade 1 C SDS IT Sulthoniyah Sambas for the 2022-2023 academic year; 2) To describe and analyze the implementation of strategies in improving writing skills with the drill method in grade 1 C SDS IT Sulthoniyah Sambas for the 2022-2023 academic year.; and 3) To describe the evaluation of strategies in improving writing skills with the drill method in grade 1 C SDS IT Sulthoniyah Sambas for the 2022-2023 academic year. This research uses qualitative approach and phenomenological type. Data collection techniques use observation, interviews, and documentation. Data analysis techniques use data collection, data reduction, data presentation, and conclusions. The technique of checking the validity of data uses triangulation and member check. The results showed that: Strategy planning in improving writing skills with the drill method in class 1 C, namely from formulating goal achievement, determining material or materials, and determining tools or media. Implementation of strategies in improving writing skills with the drill method in class 1 C including through the stage of conveying the objectives of the drill method, the stage of providing motivation, and the stage of doing exercises. Evaluation of strategies in improving writing skills with the drill method in class 1 C, namely written tests and oral tests. The written test is where the teacher tells students to write by looking at the blackboard or in the LKS book, and the oral test is where the teacher tells students to write dictatedly.